Polystyrene nanoplastics induced transgenerational reproductive toxicity in Caenorhabditis elegans through enhanced DNA damage accompanied by DNA repair inhibition - Li, Fanghao; Xu, Xinran; Wang, Zhiyuan; Xie, Jianjun; Wei, Siyang; Ji, Zhenglei; Liu, Lu; Wu, Huazhang; Zhao, Yunli (Ecotoxicology and environmental safety, 2025)
Microplastics (MPs) are omnipresent environmental pollutants posing potential impacts on organisms. To explore the transgenerational effects of polystyrene nanoplastics (PS-NPs) and the molecular mechanisms at environmental relevant concentrations, Caenorhabditis elegans (C.elegans) was applied as an in vivo model. Worms were incubated with PS-NPs at environmental concentrations from L1 larvae stage, while subsequent generations (F1 −F3) were maintained under non-exposure condition. Reproductive potential was estimated based on brood size, fertilized eggs, oocytes, and germline apoptosis. Results indicated that PS-NPs induced transgenerational toxicity in inhibiting reproductive ability, impairing gonad development, and promoting germline apoptosis. And these adverse effects were associated with dysregulated expression of apoptosis-related genes. Furthermore, DNA damage was participated in enhancing germline apoptosis through activating DNA damage checkpoint kinase ATL-1 and p53 ortholog CEP-1. Additionally, PS-NPs reduced the expression of DNA recombination repair protein RAD-51 across generations. This study demonstrates that reproductive toxicity evoked by PS-NPs can be transmitted to offspring by inducing DNA damage through activating ATL-1 and CEP-1, while simultaneously inhibiting DNA repair. [Display omitted] •PS-NPs induced transgenerational reproductive toxicity.•PS-NPs enhanced transgenerational DNA damage in germline.•DNA damage checkpoint kinase ATL-1 is essential in the toxic effects of PS-NPs.•p53 ortholog CEP-1 is essential in the toxic effects of PS-NPs.•DNA repair is involved in transgenerational reproductive toxicity.